Description of Polypharmacy and Interactions that can Reduce the Effectiveness of Dyspepsia Drugs in patient BPJS with Dyspepsia at the Porsea Regional General Hospital based on Prescriptions Period November-January 2020 - Meliani Dwi Lestari; Rosanto Tamba; Melati Silaban (CV. AFDIFAL MAJU BERKAH, 2023)
Dyspepsia is a collection of symptoms of pain, persistent or recurring discomfort in the upper abdomen, feeling full when eating, feeling full quickly, bloating, belching, decreased appetite, nausea, vomiting. Dyspepsia ranks 5th out of the top 10 diseases in hospitalized patients and 6th for outpatients. The prevalence of dyspepsia varies between 7-45%, depending on the definition used in geographic location. The prevalence in Asia is around 8-30%. It is estimated that 30% of patients who come to the gastroenterologist's practice are 60% with complaints of dyspepsia, around 20-40% of adults experience dyspepsia, whereas in general clinics it is only 2-5%. This study aims to Description of Polypharmacy and Interactions that can Reduce the Effectiveness of Dyspepsia Drugs in patient BPJS with Dyspepsia at the Porsea Regional General Hospital based on Prescriptions Period November-January 2020. The research design was descriptive with a retrospective time approach carried out at Porsea Hospital, Toba Regency, based on prescriptions for the period November-Januari 2020, data were collected in February 2020 with a sample of 118 cases using the Simple random sampling technique (November: 41 cases, December: 38 cases, January 39 cases). The instrument used to collect data in this study is the data collection format. The results showed polypharmacy in outpatient BPJS patients with dyspepsia at the Porsea Regional General Hospital for the period November-January 2020, namely 71 (60.17%) cases with major polypharmacy (5-11) and 47 (39.83%) cases with minor polypharmacy. For future researchers to examine the effects of the use of polypharmacy on reducing the effectiveness of dyspepsia drugs with guide books or other references.